FSGHF3 and peptides, prepared from fish skin gelatin, exert a protective effect on DSS-induced colitis via the Nrf2 pathway. Issue 1 (11th December 2019) - Deng, Zhao; Cui, Chenbin; Wang, Yanan; Ni, Jiangjin; Zheng, Liufeng; Wei, Hong-Kui; Peng, Jian
Abstract : Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is a chronic inflammatory disease affecting the colon, and its incidence is rising worldwide. Abstract : Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is a chronic inflammatory disease affecting the colon, and its incidence is rising worldwide. We previously found that fish skin gelatin hydrolysate fraction 3 (FSGHF3), isolated from fish skin gelatin hydrolysate, could exert antioxidant effects and maintain tight junctions in IPEC-J2 cells. Further HPLC-ESI-QqQ-MS results revealed that this fraction mainly included some peptides. Here, we aim to evaluate the effects of FSGHF3 and peptides in the mice model of dextran sodium sulfate (DSS)-induced colitis and LPS induced inflammation in IECs. The results show that FSGHF3 significantly ameliorates the clinical symptoms of DSS-induced colitis in mice, such as weight loss, disease activity index (DAI), colon shortening, spleen hypertrophy, histological scores, and MPO activity. FSGHF3 and peptide treatment inhibits pro-inflammatory cytokine production, leading to the maintenance of intestinal architecture in vivo and in vitro . Meanwhile, FSGHF3 and peptide treatment promotes antioxidant enzyme expression via activating Nrf2, which results in the removal of ROS and inhibition of NF-κB activation. Overall, our results suggest that FSGHF3 and peptides may be promising potential candidates for the alleviation of colitis.